B cells: no longer bystanders in liver fibrosis - Bhogal, Rashpal K. (American Society for Clinical Investigation, 2005)
Cytokines secreted by cells that mediate the innate and adaptive immune responses play a critical role in regulating the synthesis of ECM components by fibroblasts. Overexpression and deposition of ECM components are dominant features of fibrotic diseases, including hepatic fibrosis. The contribution of CD4(+) Th2 cells to hepatic fibrosis has been well described. Now, in this issue of the JCI, Novobrantseva et al. provide data to suggest that hepatic B cells also play a role in liver injury. In a carbon tetrachloride–induced mouse model of hepatic fibrosis, T cell–deficient mice developed severe liver fibrosis; however, in B cell–deficient animals, hepatic fibrosis was attenuated. This study provides new insight into our understanding of the cells involved in mediating the adaptive immune response that leads to hepatic fibrosis.